2011
DOI: 10.1016/j.ibusrev.2010.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Venture capital and internationalization

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 48 publications
(23 reference statements)
2
43
0
Order By: Relevance
“…While no evidence exists that VCs' cross-border deals offer higher expected returns than their local deals, findings from recent empirical studies suggest that return differences spur cross-border deals. These studies document that worldwide venture capital flows between the VC and PC countries respond positively to the expected growth in the PC country and negatively to that in the VC country (Schertler and Tykvová 2011). Moreover, countries with developed national systems of innovation, which generate more promising investment opportunities, attract larger cross-border venture capital flows than countries with less developed national systems of innovation.…”
Section: Participation In Cross-border Dealsmentioning
confidence: 92%
See 2 more Smart Citations
“…While no evidence exists that VCs' cross-border deals offer higher expected returns than their local deals, findings from recent empirical studies suggest that return differences spur cross-border deals. These studies document that worldwide venture capital flows between the VC and PC countries respond positively to the expected growth in the PC country and negatively to that in the VC country (Schertler and Tykvová 2011). Moreover, countries with developed national systems of innovation, which generate more promising investment opportunities, attract larger cross-border venture capital flows than countries with less developed national systems of innovation.…”
Section: Participation In Cross-border Dealsmentioning
confidence: 92%
“…More specifically, U.S. VCs invest into countries with a higher patenting activity Guillén 2010a, 2010b), and VCs located worldwide target countries with more university students (Aizenman and Kendall 2008) and higher business R&D expenditures (Schertler and Tykvová 2011). Finally, countries with more viable financial markets, which promise better exit possibilities and therefore better return opportunities (Black and Gilson 1998), attract larger cross-border venture capital inflows than countries with poor financial markets (Guler and Guillén 2010a, 2010b, Aizenman and Kendall 2008, Schertler and Tykvová 2011. These findings indicate that VCs cross borders when they expect higher returns abroad than at home.…”
Section: Participation In Cross-border Dealsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that venture capitalists mostly invest in small countries in which some renowned companies are founded. These funds invest more in companies dealing with IT, mechanical engineering and biotechnology than in other industries (Schertler & Tykvová, 2009). There are about 800 venture capital funds in the US.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature is replete with strategies to reduce asymmetry of information vis-à-vis portfolio firm by utilizing staging, due diligence, and monitoring portfolio firm performance (Schertler & Tykvova, 2011;Wiltbank, 2005;Zhang, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%